Antibacterial and anti-inflammatory polyethyleneimine/polyacrylic acid hydrogel loaded with CeO2 quantum dots for wet tissue wound dressings - Hou, Wenxue; Lin, Zehui; Xia, Xiaomin; Sun, Sa; Niu, Zhaojun; Liu, Jie; Lu, Jiqing; Yin, Dongming; Li, Xue (Frontiers in Materials, 2024)
Searching for an antibacterial and anti-inflammatory dressing that can stably adhere to wet tissues remains a momentous clinical challenge, especially in the context of treatment failure due to multidrug-resistant bacteria. With a hard template method in combination with an in-situ chelating strategy, three-dimensional nitrogen-doped graded porous carbon anchored 1.5-2.5 nm CeO2 quantum dots (CeO2-QDs) was tailor-designed in this study. With the aid of the size effect, CeO2-QDs have elevating percentage of Ce 3+ and oxygen vacancies that could amplify the antibacterial effects. Polyethyleneimine/polyacrylic acid (PEA) powder could self-gelling and adhesive due to the strong physical interactions, which make it an ideal carrier for CeO2-QDs. PEA@50(mg/mL)CeO2-QDs hydrogel and PEA@75(mg/mL)CeO2-QDs hydrogel with moderate doses of CeO2-QDs show a superior antibacterial effect against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) strains.